2022
DOI: 10.1186/s13011-022-00472-4
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of the Good Samaritan Drug Overdose Act among people at risk of witnessing an overdose in British Columbia, Canada: a multi-methods cross sectional study

Abstract: Introduction Bystanders to drug overdoses often avoid or delay calling 9–1-1 and cite fear of police involvement as a main reason. In 2017, the Good Samaritan Drug Overdose Act (GSDOA) was enacted by the Canadian government to provide people present at an overdose with legal protection from charges for simple drug possession, and conditions stemming from simple possession. Few studies have taken a multi-methods approach to evaluating the GSDOA. We used quantitative surveys and qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This study consisted of semi-structured, one-on-one interviews conducted by phone or in-person as part of two qualitative studies performed across BC: the Concurrent Use and Transition to Methamphetamine among People at Risk of Overdose (CUT Meth OD) study (n = 27) and the Good Samaritan Drug Overdose Act (GSDOA) evaluation study (n = 35) [28,29]. Qualitative interview guides were developed by the research team -including researchers, people with lived and living experience of substance use, stakeholders from community organizations, health authorities, and young adults.…”
Section: Methodsmentioning
confidence: 99%
“…This study consisted of semi-structured, one-on-one interviews conducted by phone or in-person as part of two qualitative studies performed across BC: the Concurrent Use and Transition to Methamphetamine among People at Risk of Overdose (CUT Meth OD) study (n = 27) and the Good Samaritan Drug Overdose Act (GSDOA) evaluation study (n = 35) [28,29]. Qualitative interview guides were developed by the research team -including researchers, people with lived and living experience of substance use, stakeholders from community organizations, health authorities, and young adults.…”
Section: Methodsmentioning
confidence: 99%
“…Concerns for the impact of knowledge disparities has been echoed in other studies where legal protections from drug policies were limited. For instance, the benefits of Canada's Good Samaritan Drug Overdose Act were inflated amongst PWUD who believed that warrants and drug trafficking were covered under the legislation [25,60]. Ample research demonstrates the impact of misunderstanding drug-related good Samaritan laws include ongoing hesitation to calling 9-1-1 in the event of an overdose, and an ongoing fear and distrust towards police, the legal system, and government in general [39,60,66].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that approximately two-thirds of PWUD in our study were aware of decriminalization is slightly elevated compared with other studies that have examined PWUDs’ awareness of drug policy reforms. A study conducted in BC on awareness of Canada’s Good Samaritan Drug Overdose Act in 2020 found that just over half of PWUD were aware of the reform [ 60 ], while other jurisdictions report lower awareness of local drug-related good Samaritan laws [ 50 , 52 , 61 ]. Awareness of other drug policies among PWUD globally are considerably lower.…”
Section: Discussionmentioning
confidence: 99%
“…One reason why Good Samaritan Laws may not be achieving greater impact is that, in many communities, the protections offered by the laws are not fully understood by potential bystanders. Studies have shown that awareness and correct knowledge of locally applicable Good Samaritan Laws remains low among people who use drugs and potential bystanders [ 15 18 ]. Better knowledge of Good Samaritan Laws has generally been associated with an increased frequency of bystanders calling 911 and otherwise seeking medical help when witnessing an overdose [ 16 , 19 21 ].However, even when knowledge about the laws is correct, distrust of law enforcement and fear of legal consequences may stand in the way of bystanders seeking help [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%